Efficacy and Safety of Ticagrelor Versus Prasugrel in Women and Men with Acute Coronary Syndrome: A Pre-specified, Sex-Specific Analysis of the ISAR-REACT 5 Trial - Gewalt, Senta; Lahu, Shqipdona; Ndrepepa, Gjin; Pellegrini, Costanza; Bernlochner, Isabell; Neumann, Franz-Josef; Menichelli, Maurizio; Morath, Tanja; Witzenbichler, Bernhard; Woehrle, Jochen; Hoppe, Katharina; Richardt, Gert; et al. (Journal of Atherosclerosis and Thrombosis, 2022)
Aim: Sex-specific analyses of direct head-to-head comparisons between newer P2Y12 inhibitors are limited. This study was conducted to assess the efficacy and safety of ticagrelor versus prasugrel in women and men with acute coronary syndromes (ACS) planned for an invasive strategy. Methods: This pre-specified analysis of the ISAR-REACT 5 trial included 956 women and 3,062 men with ACS randomly assigned to either ticagrelor or prasugrel. The primary endpoint was the 12-month incidence of death, myocardial infarction, or stroke; the safety endpoint was the 12-month incidence of bleeding (type 3–5 according to the Bleeding Academic Research Consortium [BARC]). Results: The primary endpoint occurred in 42 women (8.9%) in the ticagrelor group and 39 women (8.3%) in the prasugrel group (hazard ratio [HR] =1.10, 95% confidence interval [CI] 0.71–1.70, P =0.657) and in 142 men (9.4%) in the ticagrelor group and 98 men (6.5%) in the prasugrel group (HR =1.47 [1.13–1.90], P=0.004; P for interaction [Pint] =0.275). BARC type 3–5 bleeding occurred in 36 women (9.7%) in the ticagrelor group and 34 women (9.7%) in the prasugrel group (HR =1.04 [0.65–1.67], P=0.856) and in 59 men in the ticagrelor group (4.4%) and 46 men (3.6%) in the prasugrel group (HR=1.24 [0.85–1.83], P =0.266; Pint=0.571). Conclusions: Although there was no significant interaction between sex and treatment effect of study drugs, the superior efficacy of prasugrel was more evident among men. No difference in bleeding between the two study groups was seen for both women and men.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Acute coronary syndrome; Percutaneous coronary intervention; Prasugrel; Sex; Ticagrelor